2000
DOI: 10.1152/ajpregu.2000.278.1.r271
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod regulates arcuate nucleus POMC, AGRP, and leptin receptor mRNA in Siberian hamster hypothalamus

Abstract: Siberian hamsters decreased body weight by 30% during 18 wk in short day (SD) vs. long day (LD) controls. Subsequent imposed food deprivation (FD; 24 h) caused a further 10% decrease. In the hypothalamic arcuate nucleus (ARC), SDs reduced proopiomelanocortin (POMC) gene expression and agouti-related protein (AGRP) mRNA was elevated, changes that summate to reduced catabolic drive through the melanocortin receptors. There was no effect of photoperiod on neuropeptide Y (NPY), melanin concentrating hormone, orexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
141
6

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(170 citation statements)
references
References 51 publications
(65 reference statements)
23
141
6
Order By: Relevance
“…Possible reasons are: (i) gene expression for AGRP was unresponsive to the increasing circulating concentrations of insulin and leptin, (ii) AGRP had a greater response time than NPY to the circulatory changes in insulin and leptin, (iii) there was a greater initial level of expression in animals of the HI group, attributable to their low initial BC, and expression was still decreasing after 4 weeks, or (iv) AGRP gene expression is regulated by other factor(s). Since AGRP and NPY mRNAs are co-expressed within the ARC of rodents (Mercer et al 2000), findings from the present study suggest either that there was transcriptspecific regulation within NPY/AGRP-expressing neurons or that different neuronal sub-populations were activated.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Possible reasons are: (i) gene expression for AGRP was unresponsive to the increasing circulating concentrations of insulin and leptin, (ii) AGRP had a greater response time than NPY to the circulatory changes in insulin and leptin, (iii) there was a greater initial level of expression in animals of the HI group, attributable to their low initial BC, and expression was still decreasing after 4 weeks, or (iv) AGRP gene expression is regulated by other factor(s). Since AGRP and NPY mRNAs are co-expressed within the ARC of rodents (Mercer et al 2000), findings from the present study suggest either that there was transcriptspecific regulation within NPY/AGRP-expressing neurons or that different neuronal sub-populations were activated.…”
Section: Discussionmentioning
confidence: 64%
“…The CART probe was generated from a cloned sheep cDNA as described previously (Barrett et al 2001). AGRP and POMC probes were generated from cloned Siberian hamster cDNAs (Mercer et al 2000) and have been validated on sheep brain tissue . Briefly, sections were fixed, acetylated, and hybridised overnight at 58 C using 35 S-labelled cRNA probes (1-1·5 107 c.p.m./ml).…”
Section: Hypothalamic Gene Expressionmentioning
confidence: 99%
“…This indicated that testosterone, circulating concentrations of which would have been elevated in SD given the increased testis size (Lincoln & Davidson 1977), might be either directly down-regulating AGRP gene expression or indirectly facilitating down-regulation of AGRP by SD. Such an effect of testosterone has not been reported in the literature but it is noteworthy that AGRP gene expression is conversely decreased in male Siberian hamsters in LD when their circulating testosterone is highest (Mercer et al 2000b). Furthermore, AGRP gene expression was decreased in SD hamsters given subcutaneous implants to raise systemic testosterone concentrations (J G Mercer, personal communication) and AGRP gene expression is apparently not regulated by photoperiod in female Siberian hamsters .…”
Section: Nutritional Status and Hypothalamic Gene Expression · Z A Armentioning
confidence: 96%
“…The NPY probe was generated from a 500 bp fragment of rat prepro-NPY cDNA and has been validated for use on sheep tissues (Adam et al 1997). The CART probe (used only in experiment 2) was generated from a cloned sheep 299 bp cDNA as described previously (Barrett et al 2001), and AGRP and POMC probes were generated from cloned Siberian hamster cDNA fragments of 229 bp and 344 bp respectively (Mercer et al 2000b) and have been validated in sheep brain . Briefly, sections were fixed, acetylated and hybridised overnight at 58 C using 35S-labelled cRNA probes (1-1·5×10 7 c.p.m./ml).…”
Section: In Situ Hybridisationmentioning
confidence: 99%
“…After 12-18 weeks, hamsters lose approximately 30-40% of their initial body mass, with more than half of this being attributed to mobilization of fat reserves (Ebling 1994, Bartness 1996, Klingenspor et al 2000, Mercer et al 2000. In contrast, Syrian hamsters and collared lemmings have their maximum body masses in the winter (Bartness & Wade 1985).…”
Section: Studies Of Other Speciesmentioning
confidence: 99%